2016
DOI: 10.1111/ner.12366
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Vasopressin and Arginine Vasopressin Receptor 1b Involved in Electroacupuncture-Attenuated Hypothalamic-Pituitary-Adrenal Axis Hyperactivity in Hepatectomy Rats

Abstract: ObjectiveThe study aims to know the effect of electroacupuncture (EA) in maintenance of the homeostasis of the neuroendocrine system in hepatectomy rats and the involvement of arginine vasopressin (AVP) signaling in hypothalamus after EA was observed.Materials and MethodsRats were randomly assigned to four groups, including the intact group, model group, sham‐EA group, and EA group. EA was given during the perioperative period at the Zusanli (ST36) and Sanyinjiao (SP6) points after hepatectomy. The serum adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…However, there was no evidence concerning hypothalamic miRNAs in the modulation of the HPA axis function. Our previous study proved that EA could attenuate the hyperactivity of the HPA axis in hepatectomy rats (Zhu et al, 2016 ), but whether miRNAs were involved in the EA regulation effect of HPA axis in hepatectomy was still a question.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there was no evidence concerning hypothalamic miRNAs in the modulation of the HPA axis function. Our previous study proved that EA could attenuate the hyperactivity of the HPA axis in hepatectomy rats (Zhu et al, 2016 ), but whether miRNAs were involved in the EA regulation effect of HPA axis in hepatectomy was still a question.…”
Section: Introductionmentioning
confidence: 98%
“…The hypothalamus pituitary adrenal (HPA) axis plays an inevitable role in controlling the stress reaction, especially those induced by surgery and severe injury (Gibbison et al, 2013 ). Electroacupuncture (EA) has been proven to normalize the HPA axis dysfunction during surgery (Zhu et al, 2016 ), but its potential mechanism still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stimulation of E36 activated the limbic system (Hui et al 2005) and F3 caused limbic-cortical deactivation (Fang et al 2007). Moreover, the HPA axis activity was altered by EEA (Xu et al 2004, Sun and Wang 2007, Zhu et al 2015, Le et al 2015. It has been suggested that the ability of one particular stimulus 1010 RICARDO M. BASSETTO et al…”
Section: Discussionmentioning
confidence: 99%
“…Two observers blinded to the brain conditions were enrolled to analyze the immunohistochemical-stained brain slides. For AVP expression in the hypothalamus, immunofluorescence was performed as previously described, with some alterations [11]. Slices were washed in PBS for 30 min at room temperature and blocked with 10% normal goat serum before being incubated in a rabbit monoclonal antibody against AVP (1 : 100; Phoenix Pharmaceuticals, Burlingame, CA, USA) diluted in 0.01 mol/l PBS containing 1% bovine serum albumin, 0.02% sodium azide, and 0.03% Triton X-100 at 4°C overnight.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%